Essentials of Biostatistics & Research Methodology - Bahurupi, Yogesh; Sai, Bheemisetti Manideep (Indian Journal of Community Health, 2020)
The 3rd edition of “Essentials of Biostatistics & Research Methodology” by Dr. Indranil Saha & Dr. Bobby Paul is one of the complete books on Biostatistics & Research Methodology for Undergraduates, Postgraduates & Ph.D. students of health disciplines. It contains 11 chapters of Essential Biostatistics which are explained from basic to higher statistical concepts in an easy, understandable language by using appropriate examples, tables, diagrams wherever possible. Chapter 1 explains basic data & its presentation with maximum examples accurately. Estimation of sample size is explained excellently with formulae, examples for each study method. Sampling technique and variability, correlation, regression concepts are explained in a way they gave complete insight into the concepts. The advanced topics are a good guide for biostatisticians.